Using Pulmonary Function Data to Assess Outcomes in the Endoscopic Management of Subglottic Stenosis. (February 2015) - Kraft, Shannon M.; Sykes, Kevin; Palmer, Andrew; Schindler, Joshua
Objective: This study aimed to examine the authors' experience with endoscopic management of idiopathic subglottic stenosis (iSGS), and to identify pulmonary function test (PFT) values that can be used to quantify outcomes. Methods: Retrospective review. Results: Twenty-five patients with a new diagnosis of iSGS were seen between 2006 and 2012. Median age at surgery was 45.3 years (interquartile range [IQR], 38.5-67.0), and median body mass index was 28.7 kg/m 2 (IQR, 23.5-32.1). Forty-five procedures were performed. Median preoperative stenosis was 56.8% (Cotton-Myer grade 2). The typical stenosis began 15 mm below the true vocal folds and was 12 mm long. Median follow-up was 21.4 months (IQR, 5.1-43.1). For patients receiving multiple dilations, median time between procedures was 23.7 months. Four PFT parameters demonstrated significant improvement after intervention: (1) PEF (absolute change = 2.54 L/s), (2) PIF (absolute change = 1.57 L/s), (3) FEV1/PEF (absolute change = 0.44), and (4) FIF50% (absolute change = 1.71 L/s). PIF was the only parameter affected by using a larger balloon ( P = .047). Conclusion: PEF, PIF, FEV1/PEF, and FIF50% improved significantly after endoscopic incision and dilation of iSGS, and this could potentially be used as a metric by which to evaluate outcomes in the endoscopic management of subglottic stenosis.